They wanted dancing and not merely the lambeth walk: A reasessment of the 1940s school disturbances with particular reference to Lovedale - Kros, Cynthia (My University, 1982)
The number of so-called disturbances in African educational institutions escalated dramatically in the decade between the mid 1930s and 1946. ‘Disturbance’ was a euphemism that covered a wide range of incidents from class boycotts to arson, fairly frequently being so serious as to cause the authorities to call in the police to restore order. The ‘disturbance’ that sent the deepest shock waves reverberating through the Liberal mission network was that at Lovedale on Wednesday, August 7, 1946. It is also the best documented. The principal, Robert Shepherd, compiled and collated a mass of information in an apparent attempt to justify his course of action. In reading his account of the riot at Lovedale, it is as well to make allowances for sensationalism and his sense of moral outrage. … The assumption underlying the spotlighting of the 1940s often appears to be that the new politics was the progenitor of contemporary opposition politics; that it spawned its analysis of society, its symbols and its strategies. Yet, the school disturbances are usually only very loosely associated with a rather ill-defined militancy in the wider society. This paper argues for a much closer alignment between the kind of political analyses and strategies for action that were being developed within the walls of institutions such as Lovedale, and those that were being formulated in the hurly burly of mass-based organisational politics beyond. It also questions the assumptions about the purely urban content of the school riots and boycotts of the 1940s. Finally, it queries the rather romantic assumptions that there were certain kinds of symbolic continuity between the school politics of the 1940s and the uprisings and boycotts of the 1970s. It is the hope of the author that by dismantling romantic assumptions and probing the specific nature of school disturbances in the 1940s, a clearer picture of African schooling under late segregation will emerge, which will provide some crucial clues to a more precise apprehension of the ideological origins and initial success, from the state's point of view, of Bantu Education.
African Studies Seminar series. Paper presented 27 July 1992
Keywords: Students. South Africa. Lovedale. Attitudes; Lovedale (South Africa). Attitudes; Student strikes. South Africa. Lovedale